ANALYSIS METHOD OF ALTMAN Z SCORE MODIFICATIONS TO PREDICT FINANCIAL DISTRESS ON THE COMPANY GO PUBLIC SUB SECTOR OF THE AUTOMOTIVE AND COMPONENTS - Suhesti Ningsih; Febrina Fitri Permatasari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2018)
This research aims to analyze the variables from methods of Altman Z Score Modification in predicting financial distress in go public company automotive sub sector and component 2012-2016 periods. The results of the analysis using the method of Altman Z Score Modifications show that companies in the automotive sector and sub components of almost every year there are enterprises that are predicted to have experienced financial distress. In 2012 the company predicted experience financial distress is GDYR, the year 2013 there are 2 companies i.e. BOLT and GDYR, the year 2014 they are IMAS GDYR and predictable. In the year 2015 there are 2 companies i.e. IMAS, GDYR and 2016 year whereas LPIN is GDYR, IMAS and PRAS. The results of the analysis of the average value of Z